Peran Komunikasi Interpersonal dalam Menciptakan Keharmonisan Antar Guru dalam Lingkungan Kerja - Indah Mayasari; Dini Shaleha; Afwan Syahril Manurung (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Interpersonal communication plays an important role in creating a harmonious work environment in schools. As a central figure in education, teachers need effective communication to build strong collaboration and achieve common goals. However, different classroom management perspectives and power relationships can create conflicts and misunderstandings among teachers, which can negatively impact individual and team performance. The purpose of this study is to find out the importance of interpersonal communication in building harmony between teachers and its positive impact on teaching quality. The research methods used are literature reviews and narrative reviews that analyze data from various international journals and previous research papers. The results of the study show that good interpersonal communication can strengthen trust and mutual respect between teachers, facilitate access to information and decision-making, as well as prevent conflicts and improve work efficiency. Effective interpersonal communication has also been proven to increase teacher motivation and job satisfaction, as well as have a positive impact on the quality of student education.